2016
DOI: 10.18203/2349-2902.isj20161134
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the outcome of non-operative management in blunt abdominal solid organ injury

Abstract: INTRODUCTIONBlunt injury to abdomen is one of the most common injuries caused by road traffic accidents. It can also result from fall from height, assault with blunt objects, industrial mishaps, sport injuries, bomb blast etc. The rapid deceleration cause the shearing force to tear tissues at interfaces between tissues that are relatively fixed compared to surrounding structures or crush the tissues between external force and vertebral column or rapidly raise the intra-abdominal pressure from external compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Blunt injury of abdomen as one of the most common injuries caused by road traffic accidents has been reported by many studies. [10] John S et al [9] also reported most common mode of injury was due to Road traffic accidents in their study from Chennai.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Blunt injury of abdomen as one of the most common injuries caused by road traffic accidents has been reported by many studies. [10] John S et al [9] also reported most common mode of injury was due to Road traffic accidents in their study from Chennai.…”
Section: Discussionmentioning
confidence: 88%
“…Mortality was also higher in the converted group in study done in Oman by Raza M. [29] . John S et al [9] reported that mortality was also higher in the operative group. Malhotra et al [31] and Schroeppel and Croce [32] reported that non-operative management significantly improved outcomes over operative managements in terms of decreased abdominal infections, decreased transfusions and decreased lengths of stay.…”
Section: Discussionmentioning
confidence: 95%